Love in the Time of Migration: Lovers’ Correspondence between Italy and Canada, 1948-1957 - Cancian, Sonia (Diversité urbaine)

(untitled) (Groupe de recherche diversité urbaine, 2011)
How did a lover’s letter help to negotiate physical absence, separation, and migration? How can words of romantic love and yearning contribute to historians’ understanding of amour-passion, letter-writing, and transnational relationships? And, finally, what do they tell us about ordinary lives and migration experiences? In this article, I argue that love letters written by everyday writers in a context of international migration are extraordinary historical documents. These cultural artefacts offer a plethora of insights on transnational communication, the romantic love that infused such epistolary narratives, the challenges that ordinary lovers faced in their separation, and how letter-writing helped them to negotiate a lover’s absence. Letters written by women and men in the context of Italian postwar migration to Canada are employed to illustrate my points.